Investigation of impurity confinement in lower hybrid wave heated plasma on EAST tokamak. (1st November 2017) - Xu, Z.; Wu, Z.W.; Zhang, L.; Gao, W.; Ye, Y.; Chen, K.Y.; Yuan, Y.; Zhang, W.; Yang, X.D.; Chen, Y.J.; Zhang, P.F.; Huang, J.; et al.
Abstract: The transient perturbation method with metallic impurities such as iron (Fe, Z   =  26) and copper (Cu, Z   =  29) induced in plasma-material interaction (PMI) procedure is used to investigate the impurity confinement characters in lower hybrid wave (LHW) heated EAST sawtooth-free plasma. The dependence of metallic impurities confinement time on plasma parameters (e.g. plasma current, toroidal magnetic field, electron density and heating power) are investigated in ohmic and LHW heated plasma. It is shown that LHW heating plays an important role in the reduction of the impurity confinement time in L-mode discharges on EAST. The impurity confinement time scaling is given as 42 I P 0.32 B t 0.2 n ̄ e 0.43 P t o t a l − 0.4   on EAST, which is close to the observed scaling on Tore Supra and JET. Furthermore, the LHW heated high-enhanced-recycling (HER) H-mode discharges with ~25 kHz edge coherent modes (ECM), which have lower impurity confinement time and higher energy confinement time, provide promising candidates for high performance and steady state operation on EAST.